4A.03: CATHETER-BASED RENAL DENERVATION FOR RESISTANT HYPERTENSION. (June 2015) - Tsioufis, C.; Papademetriou, V.; Dimitriadis, K.; Kasiakogias, A.; Kordalis, A.; Thomopoulos, C.; Tsiachris, D.; Tousoulis, D.; Worthley, S.
Abstract : Objective: The EnligHTN I, the first-in-human study using a multielectrode ablation system for renal denervation (RDN) in patients with drug resistant hypertension (dRHT) demonstrated efficacy and safety at 6 and 12 months. The aim of this study was to report the complete set of 24 month data on office, ambulatory and home blood pressure (BP) changes as well as long term safety. Design and method: We studied 46 patients (age: 60±10 years, 4.7 ± 1.0 antihypertensive drugs, body mass index: 32 ± 5 kg/m 2 ) with dRHT on >or=3 antihypertensive medications who had a systolic BP>or=160 mmHg (>or=150 mmHg for diabetics). At baseline, the average office BP, 24-hour ambulatory BP and home BP were 176 ± 16/96 ± 14 mmHg, 150 ± 14/83 ± 13 mmHg and 158 ± 16/90 ± 12 mmHg respectively. Bilateral RDN was performed using percutaneous femoral approach and standardized techniques. Results: Reduction in office BP at 18 and 24 months from baseline were -24/-10 mmHg and -29/-13 mmHg, while the reduction in 24-hour ambulatory BP and in home BP at 24 months were -13/-7 mmHg and -11/-6 mmHg respectively (p < 0.05 for all). Apart from higher body mass index (33.3 ± 4.7 vs 29.5 ± 6.2 kg/m 2, p < 0.05), there were no differences in age, baseline office BP, heart rate, diabetes mellitus and baseline antihypertensive drug therapy in patients that were RDN responders at 24 months [defined as 10 mmHg decline in office BP compared to baseline (74%, n = 34)]. Stepwise logistic regression analysis revealed no prognosticators of RDN response (p = NS for all). At 24 months apart from a trend for renal function decrease, there were no new serious or life-threatening adverse events related with the procedure. Conclusions: The EnligHTN I study provides evidence that the multielectrode ablation system constitutes a safe method of RDN in patients with dRHT and is accompanied by a sustained reduction of office, ambulatory and home BP at 24 months after the procedure. However, no predictors of RDN response were identified at long term follow-up.